2018
DOI: 10.1021/jacs.8b03735
|View full text |Cite
|
Sign up to set email alerts
|

Spin State Chemistry: Modulation of Ligand pKa by Spin State Switching in a [2×2] Iron(II) Grid-Type Complex

Abstract: The iron(II) [2×2] grid complex Fe-8H has been synthesized and characterized. It undergoes spin-crossover (SCO) upon deprotonation of the hydrazine-based terpyridine-like ligand. The deprotonation patterns have been determined by X-ray crystallography and H NMR spectroscopy and discussed in relation to the spin state of the iron(II) centers, which influences greatly the p K of the ligand. The synthesis of the magnetically silent zinc(II) analogue is also reported, and its (de)protonation behavior has been char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
63
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 77 publications
3
63
0
Order By: Relevance
“…When triggered by ultrafast laser-excitation, which is inherently wavelength-selective, photoinduced spin-state switching (PSS) and light-induced excited spin-state trapping (LIESST) in organized arrays of TM ions constitute some of the most promising approaches for realizing the long-standing goal of initiating chemical reactions through prompt changes of spin [13][14][15][16][17] .…”
mentioning
confidence: 99%
“…When triggered by ultrafast laser-excitation, which is inherently wavelength-selective, photoinduced spin-state switching (PSS) and light-induced excited spin-state trapping (LIESST) in organized arrays of TM ions constitute some of the most promising approaches for realizing the long-standing goal of initiating chemical reactions through prompt changes of spin [13][14][15][16][17] .…”
mentioning
confidence: 99%
“…To date, very few examples of protonation‐controlled state‐switching in molecular species are known. Most recently, Lehn and co‐workers showed that the SCO behavior of a polynuclear {Fe 4 } grid‐type complex can be modified in response to pH by using protic ditopic ligands . And while mononuclear Fe II ‐complexes which reversibly respond to protonation/deprotonation are known, these systems can be switched between just two discrete states .…”
Section: Figurementioning
confidence: 99%
“…Only a few pH responsive SCO examples reported, and the modulation of magnetic properties is due to the change of the overall ligand-field strength upon ligand protonation/deprotonation. [32][33][34][35][36] Nowak et al 37 reported proton-driven coordination-induced spin-state switching (PD-CISSS) of iron(II) complexes in solution and as composite materials. Recently, we also reported successful switching of the spin state of an Fe(II) complex in solution as a result of reversible dissociation-association of the coordination sphere driven by protonation and deprotonation.…”
Section: Introductionmentioning
confidence: 99%